2017
DOI: 10.1002/ece3.3252
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic differentiation of the Solidago virgaurea complex along an elevational gradient: Insights from a common garden experiment and population genetics

Abstract: Plant species distributed along wide elevational or latitudinal gradients show phenotypic variation due to their heterogeneous habitats. This study investigated whether phenotypic variation in populations of the Solidago virgaurea complex along an elevational gradient is caused by genetic differentiation. A common garden experiment was based on seeds collected from nine populations of the S. virgaurea complex growing at elevations from 1,597 m to 2,779 m a.s.l. on Mt. Norikura in central Japan. Population gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…Stöcklin et al 2009;Št'astná et al 2012;Kim and Donohue 2013;Scheepens and Stöcklin 2013;Gugger et al 2015;Hamann et al 2016;Stöcklin and Armbruster 2016;Sakurai and Takahashi 2016;Takahashi and Matsuki 2016). Plants can respond to elevational changes based on their morphological and physiological plasticity and through local adaptations (Hirano et al 2017). Alpine plant species, compared to lowland plants, have distinctly smaller overall size (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stöcklin et al 2009;Št'astná et al 2012;Kim and Donohue 2013;Scheepens and Stöcklin 2013;Gugger et al 2015;Hamann et al 2016;Stöcklin and Armbruster 2016;Sakurai and Takahashi 2016;Takahashi and Matsuki 2016). Plants can respond to elevational changes based on their morphological and physiological plasticity and through local adaptations (Hirano et al 2017). Alpine plant species, compared to lowland plants, have distinctly smaller overall size (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Neuffer and Bartelheim 1989;Hirano et al 2017) or reciprocal transplantation to plots located at different elevations (e.g. Gonzalo-Turpin and Hazard 2009;Hautier et al 2009;Scheepens et al 2010;Hamann et al 2016) are essential.…”
mentioning
confidence: 99%
“…The latter explanation was clearly confirmed in Heliosperma pusillum (Bertel et al, ). A study of phenotypic variation within the Senecio virgaurea complex along an elevational gradient has revealed that plants originating from higher elevations have larger flower heads and shorter stems (Hirano et al, ). However, the genetic differentiation in neutral genes between populations at different elevations turned out to be extremely low.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of particular environmental conditions (a scree habitat, high elevation, and serpentine bedrock) on the morphological appearance of the Alyssum taxa under study can be addressed by common garden experiments. Simple cultivation under uniform conditions is frequently used to assess the performance of morphological traits or to detect genetically based phenotypic differentiation between cytotypes or morphotypes (e.g., Mráz et al, ; Bertel et al, ; Eliášová & Münzbergová, ; Hirano et al, ), but a detailed examination of the morphological effects of specific environmental factors would require thoroughly designed reciprocal transplant experiments (see e.g., Bastida et al, ; Yuan et al, ; Hamann et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation